SINERGI FITOKIMIA DAUN KELOR (Moringa oleifera Lam) DAN JAHE MERAH (Zingiber officinale var. rubrum) SEBAGAI ANTIINFLAMASI ALAMI PADA MENCIT JANTAN (Mus musculus): SINERGI FITOKIMIA DAUN KELOR (Moringa oleifera Lam) DAN JAHE MERAH (Zingiber officinale var. rubrum) SEBAGAI ANTIINFLAMASI ALAMI PADA MENCIT JANTAN (Mus musculus) - Nurwani, Nurwani Purnama Aji; Nabella, Innayah Azquri (Akademi Farmasi Yarsi Pontianak, 2024)
Moringa leaves contain the compound quercetin which is known as a strong antioxidant and is able to inhibit the COX-2 enzyme, while red ginger contains gingerol, which has anti-inflammatory properties through inhibiting cyclooxygenase-2 (COX-2) and pro-inflammatory cytokines. This study aims to evaluate whether the combination of Moringa leaf extract and red ginger provides a synergistic effect as an anti-inflammatory and to determine the most effective dose of this combination, considering its potential as a herbal medicine with anti-inflammatory properties. This research uses a testing method by inducing edema on the soles of mice's feet using carrageenan. The edema volume was then measured with a plethysmometer to assess the effectiveness of the extract combination. The results showed that the combination of Moringa leaf extract and red ginger provided a significant anti-inflammatory effect, especially at a combined dose of 35 mg/KgBW of moringa and 100 mg/KgBW of red ginger, with edema inhibition reaching 92.25% at time 6. However, increasing the dose of red ginger (200 mg/KgBW) produced a lower effect. This research indicates a synergistic effect from the combination of the two extracts in reducing inflammation, but dosage variations must be considered to obtain optimal effectiveness.